Effects of α lipoic acid combined with olmesartan medoxomil on blood glucose and oxidation indicators in patients with diabetic nephropathy - Shengfu Jiao, MB; Yuxia Dong, MB; Xiang Chang, MB; Yanan Wu, MB; Haifeng Li, MB (Medicine, 2022)
Abstract. Background:. Diabetic nephropathy (DN) is a common microvascular complication of diabetes, which poses a serious threat to the health and life of patients. There is evidence that both α lipoic acid and olmesartan medoxomil have positive effects in the treatment of DN, but whether the 2 have synergistic effects and the effects on blood glucose and oxidation indicators are controversial. Methods:. This is a prospective parallel, randomized, double-blind, placebo-controlled trial to study the effects of α lipoic acid in combination with olmesartan medoxomil on blood glucose and oxidation indicators in patients with DN. Participants will be randomly assigned to a treatment group, which will receive α lipoic acid dispersive tablets combined with olmesartan medoxomil tablets, or a control group, which will receive olmesartan medoxomil tablets combined with placebo for 4 weeks, followed up for 12 weeks. Observation indicators include: glycemic indicators [fasting blood glucose, 2 hours postprandial blood glucose and glycosylated hemoglobin], the oxidation indicators [serum glutathione, superoxide dismutase, malondialdehyde, 8-hydroxydeox-yguanosine], and adverse reactions. Finally, SPASS 22.0 software will be used for statistical analysis of the data. Discussion:. This study will evaluate the effects of α lipoic acid combined with olmesartan medoxomil on blood glucose and oxidation indicators in patients with DN. The results of this study will provide a reference for the clinical use of α lipoic acid combined with olmesartan medoxomil in the treatment of DN. Trial registration:. OSF Registration number: DOI 10.17605/OSF.IO/VJWXS